Modeller 2019
DOI: 10.18261/9788215034393-2019-10
|View full text |Cite
|
Sign up to set email alerts
|

10. From helicopter parenting to co-piloting: Models for regulating video gaming among immigrant youth in Norway

Abstract: SAMMENDRAG Hvordan reguleres og forhandles det rundt ungdoms dataspilling i familier med ikke-vestlig bakgrunn i Norge? Dette er spørsmålet som utforskes i dette kapitlet, som utforsker kilder for konflikt og modeller for konfliktløsning knyttet til dataspill i et familieperspektiv. Et kvalitativt empirisk materiale blir analysert i lys av diskursteori. Funnene viser at de mest harmoniske modellene er de som baserer seg på dialog, tillit og gjensidig deltaking fra ungdom og foreldre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Youth's media interests and engagements can bring about the reorganization of family everyday life and of relational interests. For instance, a research study on gaming among youth with immigrant backgrounds in Norway shows that there is a correlation between how gaming is regulated at home and parents' knowledge about this practice (Dralega et al, 2019). Parents' lack of knowledge about gaming on the one hand, alongside a limited digital media literacy among these parents on the other hand, can cause frustrations in the participating families (Livingstone & Blum-Ross, 2020).…”
Section: Collectivizing Agency: Family Members' Mutual Constitution O...mentioning
confidence: 99%
“…Youth's media interests and engagements can bring about the reorganization of family everyday life and of relational interests. For instance, a research study on gaming among youth with immigrant backgrounds in Norway shows that there is a correlation between how gaming is regulated at home and parents' knowledge about this practice (Dralega et al, 2019). Parents' lack of knowledge about gaming on the one hand, alongside a limited digital media literacy among these parents on the other hand, can cause frustrations in the participating families (Livingstone & Blum-Ross, 2020).…”
Section: Collectivizing Agency: Family Members' Mutual Constitution O...mentioning
confidence: 99%
“…As gaming has become a popular everyday activity among young people, research often looks at their video gaming habits within the family context (Aarsand & Aronsson, 2009;Ask, 2011;Dralega et al, 2019), "which is a particular and central context in Western sociality in that it is considered by most as existentially crucial and hence highly moral" (Helle-Valle & Storm-Mathisen, 2008, p. 62). Time spent gaming is argued to cause conflict with family and school obligations (Gregersen, 2018;Linderoth & Bennerstedt, 2007), making gaming highly controversial (The Ministry of Culture, 2018).…”
Section: Contextualization Of the Studymentioning
confidence: 99%
“…Helle-Valle and Storm-Mathisen (2008) argue that when parents are not involved in children's gaming, its positive aspects go unrecognized. This impacts how gaming is regulated in the family (Dralega et al, 2019). However, active mediation-i.e., practices that include youths in decision making around their media use in the family context (Clark, 2013), understood as a process of the democratization of the family-has become increasingly idealized and normalized as positive parental mediation in the Global North (Clark, 2013).…”
Section: Contextualization Of the Studymentioning
confidence: 99%
“…Gaming is a frequent source of conflict in the family. Such conflicts have been attributed to a series of deficits on the parents' part: authoritative parenting styles that are more concerned with limiting gameplay than engaging with it (Dralega et al, 2019;The Norwegian Media Authority, 2015), lack of gaming related expertise (Bergsjø et al, 2018), and a general dismissive attitude towards gaming as a pastime (Gregersen, 2018). Following this research, and the research-based advice given to parents about getting more involved with games (The Norwegian Media Authority, n.d.), is an expectation that gaming will be a relatively hassle-free element in everyday life once these deficits are addressed.…”
Section: Introduction: Gaming Parents -From Deficit To Excessmentioning
confidence: 99%
“…Where previous work on family and games assumed that parents do not play games (e.g., Dralega et al, 2019;Shin & Huh, 2011), this assumption is quickly becoming outdated. The Norwegian Parents and Media survey found that 46 per cent of parents play games (slightly higher among fathers than mothers, and lowest among older parents) (The Norwegian Media Authority, 2018).…”
Section: Introduction: Gaming Parents -From Deficit To Excessmentioning
confidence: 99%